AB0285 Correlation between serum levels of parathyroid hormone and DICKKOPF-1 in patients with rheumatoid arthritis. (23rd January 2014) - Orsolini, G.; Povino, M.R.; Tripi, G.; Caimmi, C.; Lippolis, I.; Idolazzi, L.; Fracassi, E.; Viapiana, O.; Gatti, D.; Rossini, M.; Adami, S.
Abstract : Background: It was recently observed that Dickkopf-1 (DKK-1), a natural inhibitor of Wnt signaling and bone formation, is correlated with inflammation and bone erosion in Rheumatoid Arthritis (RA) (1). We also observed that the presence of bone erosions in RA correlates with high serum Parathyroid Hormone (PTH) (2) and that the long-term treatment with PTH increases DKK-1 serum levels (3). Objectives: Objective of this study is to explore the correlation between PTH and DKK-1 serum levels in patients with RA. Methods: In serum samples from 154 patients with RA and 107 healthy controls DKK-1, 25OH vitamin D (25OHD) and PTH levels were measured by ELISA. Clinical measurements of RA disease activity included the Italian version of the Health Assessment Questionnaire Disability Index (HAQ), the Disease Activity Score 28-joint count (DAS28) and the van der Heijde modification of the Sharp erosion score. Results: The two groups were not significantly different for age, body mass index and 25OHD serum levels. The mean serum level of DKK-1 was significantly higher in patients with RA than in healthy controls (172 vs 90 pmoL/L, respectively; p=0, 0001). Patients with erosions had serum levels of DKK-1 slightly higher than those without erosions (179 vs 160 pmoL/L, respectively; p=0, 08). The serum DKK-1 levels were significantly correlated with HAQ, DAS28 and the disease duration. Mean serum levels of PTH in RA patients were 40% higher than in controls (30 vs 22 pg/ml, respectively; p=0, 0001) and were significantly correlated with DKK-1 serum levels (p<0, 0001). Conclusions: In patients with RA serum PTH and DKK-1 are significantly increased, correlated each other and account for joint bone destruction. References: Wang et al, J Rheumatol. 2011;38:821-7. Rossini et al, J Rheumatol. 2011, 38:997-2002. Gatti et al, J Clin Endocrinol Metab. 2011, 96:1555-9. Disclosure of Interest: None Declared